(untitled) (Journal of the College of Basic Education, 2022)
Consumption of foods enriched with herbs and herbal medicine products are highly popular. Their current popularity renders the assessment of their safety an urgent necessity, they must figure prominently in nutritional surveys as possible factors in cancer and some other diseases, as they may contain highly toxic chemicals and heavy metals in addition to natural organic toxins, made the present study aims to investigate the side effects of fennel seeds Foeniculum vulgare, in male rats, on the weights , histological changes and some of the physiological parameters of the liver. For this purpose, 60 Spargue-Dawley albino adult male rats were daily treated oraly with fennel seed powder mixed with rat diet in three different doses (50, 100, 200)gm/kg bodyweight(bw) in three different periods of time (10, 20, 30) days. Adult male rats were divided into 12 groups each of five rats, as following : (Group 1, 2, 3) normal control rats that were fed with chow pellet only for (10, 20, 30) days subsequently, (Group 4, 5, 6) experimental treated groups that respectively received fennel pellet in three doses of (50, 100, 200) gm/kg for 10 days, (Group 7, 8, 9) experimental treated groups that respectively received fennel pellet in three doses of (50, 100, 200) gm/kg for 20 days, (Group 10, 11, 12) experimental treated groups that respectively received fennel pellet in three doses of (50, 100, 200) gm/kg for 30 days. The end of each experiment was followed by weighing the animals, blood sample of each animal was collected by heart puncture then directly centrifuged and the serum was kept at -80 oC for biochemical analysis and some histological standards, the animals were dissected, then the liver was excised and fixed in neutral buffered 10% formalin for histological preparation. Increased doses of fennel consumption and treatment duration statistically caused: Highly significant (p<0.01) decrement in liver weights of fennel treated groups ( 7, 8, 9, 10, 11, 12) in comparison to control groups. Highly significant increment (p<0.01) in Glutamate oxaloacetate transaminase(GOT) and Glutamate pyruvate transaminase(GPT) serum levels in treated groups (5,6,7,8,9,10,11,12), while Alkaline phosphatase(ALP) serum levels showed significant increment (p<0.05) in fennel treated groups (10, 11, 12) compared to the control groups. liver sections showed sinusoidal dilatation with mild degenerative, inflammatory cells infiltration, congestion in blood vessels and necrosis. Fennel, liver, doses, necrosis.